Suvorexant, an FDA-approved dual orexin receptor antagonist, reduces oxycodone self-administration and conditioned reinstatement in male and female rats - Illenberger, Jessica M.; Flores-Ramirez, Francisco J.; Matzeu, Alessandra; Mason, Barbara J.; Martin-Fardon, Rémi (Frontiers in Pharmacology, 2023)
The Department of Health and Human Services reports that prescription pain reliever (e.g., oxycodone) misuse was initiated by 4,400 Americans each day in 2019. Amid the opioid crisis, effective strategies to prevent and treat prescription opioid use disorder (OUD) are pressing. In preclinical models, the orexin system is recruited by drugs of abuse, and blockade of orexin receptors (OX receptors) prevents drug-seeking behavior. The present study sought to determine whether repurposing suvorexant (SUV), a dual OX receptor antagonist marketed for the treatment of insomnia, can treat two features of prescription OUD: exaggerated consumption and relapse. Male and female Wistar rats were trained to self-administer oxycodone (0.15 mg/kg, i.v., 8 h/day) in the presence of a contextual/discriminative stimulus (SD) and the ability of SUV (0-20 mg/kg, p.o.) to decrease oxycodone self-administration was tested. After self-administration testing, the rats underwent extinction training, after which we tested the ability of SUV (0 and 20 mg/kg, p.o.) to prevent reinstatement of oxycodone seeking elicited by the SD. The rats acquired oxycodone self-administration and intake was correlated with the signs of physical opioid withdrawal. Additionally, females self-administered approximately twice as much oxycodone as males. Although SUV had no overall effect on oxycodone self-administration, scrutiny of the 8-h time-course revealed that 20 mg/kg SUV decreased oxycodone self-administration during the first hour in males and females. The oxycodone SD elicited strong reinstatement of oxycodone-seeking behavior that was significantly more robust in females. Suvorexant blocked oxycodone seeking in males and reduced it in females. These results support the targeting of OX receptors for the treatment for prescription OUD and repurposing of SUV as pharmacotherapy for OUD.